SAAF stakeholder co-design workshop in Son La Province, Vietnam: Workshop report - Nguyen Thi Thinh; Lo Quang Thanh; Atieno, Mary; Dao Thu Hang; Sinh Dang-Xuan; Nguyen Thi Minh Phuong; Le Thi Thanh Huyen; Nguyen Thi Quynh Chi; Marshall, Karen; Rao, E.J.O. (International Livestock Research Institute, 2025)
Sustainable Animal and Aquatic Foods (SAAF) is one of CGIAR’s eight science programs for the 2025–2030 period, with the vision to improve the lives and well-being of people in low- and middle-income countries by sustainably transforming animal and aquatic food systems. This will be achieved through six Areas of Work (AoW): Productivity+, Climate and Environment, One Health, Market Systems, Policy Solutions and Scaling, Gender, Youth, and Social Inclusion, and Digital and Data Solutions. The program operates in 17 countries globally, including Vietnam. In Vietnam, the program is implemented in the provinces of Son La and Thai Nguyen. It is coordinated by the International Livestock Research Institute (ILRI) and International Center for Tropical Agriculture (CIAT), in close partnership with national and local stakeholders. From 2019 to 2024, ILRI, CIAT and partners implemented two projects in Son La province: Li-Chan (Livestock CRP) and Chan-henh (Sustainable Animal Productivity Initiative – SAPLING). These initiatives introduced a range of models and innovations, including improved breeding techniques, biosecurity practices, high-yielding forage varieties, artificial insemination for pigs and cattle, enhanced nutrition, and approaches promoting gender equality and youth engagement. These efforts enabled local farmers to adopt more productive and sustainable livestock practices. Building on this foundation, SAAF aims to scale these innovations to improve livestock productivity, minimize environmental impacts, and strengthen gender and youth equity in the region. On 21 August 2025, ILRI and CIAT, in partnership with Son La Sub-Department of Animal Husbandry, Veterinary and Fisheries (Sub-DAH) and local authorities, jointly conducted a one-day workshop to develop a theory of change (ToC) for cattle and pigs value chains in Son La Province. The workshop brought together 34 participants representing local authorities from agriculture and environment sectors, veterinary services, and market actors (feed suppliers, farmers, cooperatives, traders, slaughterhouses).